Tax Competition in Europe - Europe in competition with other world regions? - Frank Streif (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Corporate tax levels have fallen substantially in Europe during the last decades. There is a broad literature on tax competition which has been identified as one reason for the decline in corporate tax levels. However, none of these studies explicitly ask the question whether tax competition within regions is di erent from tax competition across regions, e.g. due to "global regionalism" of foreign direct investments. This is a crucial question to answer in order to discuss the desirability of (local) tax harmonization, for example, within the European Union. Therefore, the study aims to give hints on the following questions: Is the decline in corporate tax levels in Europe mainly driven by inner-European tax competition? Or is it (also) due to pressure from other world regions? The results of this study which makes use of tax reaction functions (spatial econometrics) indicate that there is evidence for tax competition within Europe (with respect to effective average tax rates) whereas there is no evidence that European countries compete with countries from other regions.
Keywords: H20; H77; H87; 330